Pharmacological Treatments against COVID-19 in Pregnant Women - Ana Arco-Torres (MDPI AG, 2021)
The recent respiratory virus known as SARS-CoV-2 has caused millions of deaths worldwide, causing great uncertainty due to the lack of a specific treatment, which has been mitigated by the use of various drugs traditionally used against other types of pathologies. Pregnancy presents special physiological conditions that expose the pregnant woman and the foetus to greater risk. Pregnant women are often excluded from trials due to possible risk of toxicity or side effects, resulting in a lack of knowledge about the use of drugs and treatments during pregnancy. The main objective of this review was to compile existing knowledge about currently available drug treatments for COVID-19 in pregnant women. The review report met the criteria of the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) review protocol and was registered with the registration number CRD42021251036. The electronic databases searched were Scopus, PubMed, CINAHL and SciELO. Finally, 22 articles were included, resulting in an analysis of drugs with an acceptable safety profile in the treatment of pregnant women with COVID-19.